Meänkieli-svensk-meänkieli ordbok - Kangas, Elina; The National Association of Swedish Tornedalians, Tornionlaaksolaiset; Svenska Tornedalingars Riksförbund – Tornionlaaksolaiset (Swedish National Data Service, 2023)
The Meänkieli-Swedish-Meänkieli dictionary is a digital dictionary containing approximately 33 000 words with translations from Meänkieli to Swedish and from Swedish to Meänkieli. The words are marked with their respective word classes. The dictionary also contains some examples with geographical information. The dataset is comprised of about 33,000 words in Meänkieli with Swedish translations, the words are tagged with their respective word classes. The dataset consists of two parts; Meänkieli-to-Swedish and Swedish-to-Meänkieli. The files are categorized by their first letter. The fileformat is .xml, the dataset also contains a .dtd to describe the internal subset within the .xml files. Meänkieli-svensk-meänkieli ordbok är en digital ordbok som består av cirka 33 000 ord med översättningar från meänkieli till svenska och från svenska till meänkieli. Orden är märkta med ordklass. I vissa fall finns exempel och geografisk märkning. Datasetet består av c.a 33 000 ord på meänkieli med svenska översättningar, orden är även märkta med ordklass. Datamängden är uppdelad mellan meänkieli till svenska och svenska till meänkieli. Filen är kategoriserade efter begynnelsebokstav. Filmformatet är .xml, bland datamängden finns även .dtd-beskrivningen för konventionen som följs i dessa filer.